2020
DOI: 10.21660/2020.69.9242
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Destructive Method for Investigating Soil Layers of an Individual Vulnerable Slope

Abstract: Soil stability analysis becomes main concern in the preliminary design of new construction project. In a critical soil slope, the stability can be affected by the additional load and water infiltration significantly. This is due to additional overturning moment and decreasing of shear strength of the slope material. In such scenario, the non-destructive soil investigation method is needed to analyze the stability. This paper examines the use of Electrical Resistivity Tomography (ERT) to investigate soil layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Geophysical surveys are one of the most reliable ways to find a groundwater supply. The common approach for the geophysical survey is resistivity method which can identify sources of groundwater potential [1]. This method is based on the composition and layering of the subsurface, interpretation of the soil's physical characteristics, and underground structures, cavities, and bodies from various geological environments [2].…”
Section: Introductionmentioning
confidence: 99%
“…Geophysical surveys are one of the most reliable ways to find a groundwater supply. The common approach for the geophysical survey is resistivity method which can identify sources of groundwater potential [1]. This method is based on the composition and layering of the subsurface, interpretation of the soil's physical characteristics, and underground structures, cavities, and bodies from various geological environments [2].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous parametric studies have been conducted on slope geometry to evaluate the effect of slope angle and height on the vulnerability of slope failures [8][9][10]. Many studies have concluded that the higher the slope angle lower both the initial and minimum factors of safety [5,11,12]. In contrast, the reduction of the factor of safety in gentle slopes is higher than that of steeper slopes at heavy rainfall [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Geotechnical site investigation is of prime importance in ensuring the safety of civil engineering structures related to embankments, pavements and landfills [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Therefore the understanding of the soil interface shear strength is vital in designing and analysing the stability of geotechnical structures [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%